2010
DOI: 10.1109/tcsi.2009.2033528
|View full text |Cite
|
Sign up to set email alerts
|

A Design-Oriented Soft Error Rate Variation Model Accounting for Both Die-to-Die and Within-Die Variations in Submicrometer CMOS SRAM Cells

Abstract: Submicrometer static random access memory cells are more susceptible to particle strike soft errors and increased statistical process variations, in advanced nanometer CMOS technologies. In this paper, analytical models for the critical charge variations accounting for both die-to-die and within-die variations are proposed. The derived models are verified and compared to Monte Carlo simulations by using industrial 65-nm CMOS technology. This paper provides new design insights such as the impact of the coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…1) is the most susceptible to particle strikes. It has been reported that of a 0-to-1 flip in SRAM is about 22X larger than that for a 1-to-0 flip [10], [24]. When a particle strike occurs at node , the injected current pulls this node voltage down to "0" against the pMOS transistor current which tries to recover the node voltage.…”
Section: E Soft Error Rate (Ser)mentioning
confidence: 99%
See 4 more Smart Citations
“…1) is the most susceptible to particle strikes. It has been reported that of a 0-to-1 flip in SRAM is about 22X larger than that for a 1-to-0 flip [10], [24]. When a particle strike occurs at node , the injected current pulls this node voltage down to "0" against the pMOS transistor current which tries to recover the node voltage.…”
Section: E Soft Error Rate (Ser)mentioning
confidence: 99%
“…Due to NBTI, current is reduced due to the increased which reduces and increases the SER. In [10], the sensitivity of to transistor threshold voltage, , is given by:…”
Section: E Soft Error Rate (Ser)mentioning
confidence: 99%
See 3 more Smart Citations